Community dynamics in a species-rich patch of old-growth forest in a global changing scenario - Gastauer, Markus; Meira Neto, João Augusto Alves (Acta Botanica Brasilica, 2012)
Ecological theory predicts that, in mature ecosystems, species richness, the number of individuals and the biomass of individuals will remain in a relatively stable state of equilibrium. The aim of this study was to test that theory. In 2001 and 2010, we conducted censuses of all trees with a circumference at breast height > 10 cm in a one-hectare plot in a seasonal semideciduous old-growth forest in southeastern Brazil. We compared the two censuses in terms of species richness and diversity, computing growth, recruitment and mortality rates, as well as gains and losses of basal area. Between 2001 and 2010, species richness declined from 224 to 218 species and the basal area increased from 37.86 to 40.16 m2 ha-1. Overall turnover (the mean difference between mortality and recruitment) was lower than would be expected for a seasonal semideciduous forest, indicating stability and slight successional advance. This interpretation is supported by the observation that pioneer species and canopy species both showed higher mortality than recruitment. However, uncommon species (< 10 individuals in the 2001 census) showed higher mortality than recruitment and became rarer, whereas most species that were abundant in 2001 became more abundant by 2010. These observations, as well as the decline in species richness, although statistically not significant, match the predictions of ecological theory for scenarios in which formerly contiguous ecosystems become fragmented and the remnants become isolated within the landscape. Nevertheless, further censuses are needed in order to test the idea that the observed patterns are not explained by natural oscillations but are consequences of environmental changes related to human activity.
Keywords: Community dynamics; Habitat loss; Immigration rate; Landscape fragmentation; Species richness